Assessment of pea seed quality in the production zone of the Nariño department - Porras, Nelly Marcela; Riascos , Marcela Elizabeth; Romero, Juan Vicente; Revelo , Eliana Gisela; Cadena, Máryory Maricela; Riascos-Ortiz, Donald Heberth (Revista de Ciencias Agrícolas, 2025)
In Colombia, the largest pea production occurs in the south of the department of Nariño. Seed is the most important input for cultivation; however, practices used for its selection and storage can reduce its quality and viability. This research analyzed the physical, physiological, and sanitary quality of pea seeds from two sources: producers and those produced according to Colombian regulations (wineryhouse). Regarding quality variables, 58% of the samples in producer seed presented rough, whitish, or spotted grains, plant residues, and inert material. Their germination was lower than required by regulations; 75% presented a humidity percentage higher than recommended (14%). Environmental and phytopathogenic fungi were isolated, from which 15 consensus sequences of the ITS region of rRNA were obtained, allowing the identification of Alternaria sp., Botrytis sp., Stemphylium sp., Arthrinium sp., Dydimella sp., Parastagonospora sp., Penicillium sp., Verrucoconiothyrium sp., Cladosporium sp., Trametes versicolor, and Epicoccum sp. No presence of Pseudomonas spp. was detected in the seed. Potyvirus was present in 5 of the 24 samples evaluated. There were no impurities or atypical grains in the seed from the winery; germination was greater than 80% in the 24 months of evaluation, and humidity met the specifications for certified seed. The frequency of fungi and bacteria was lower than in the producers’ conditions, although Monilia sp. and Penicillium sp. were found. The seed from producers has low quality, while warehouse seed complies with Colombian regulations, highlighting the importance of improving production and storage conditions by producers.